(3GdCOhjI GdeaQOI hGdeSgdIs - (3GdfLjH GdSeQbfOj , eMeO Hf Ydj Hf YeQ GdSeQbfOj, fLjH GdOjf CHh MGeO,J (B619 (3g` s
(3ChdgG (B:s
(3gPG GdeNJUQ jfWhi Ydi PcQ GdCOhjI GdeaQOI GdeSJYedI hNhGUgG hCaYGdgG GdefShHI EdjgG MQha GdCda (B: (3Ecdjd (B: (3MGQ jGHS ai Gdhdi eMdd GdChQGe NGUI ai GdCYVGA GdYUHGfjI , hefVL dgG , ebhdLejY GdCYVGA s
(3BNQgG (B:s
(3hjfHZi Cf jchf GdeYJUQ efg GdMdh hGdMGeV eYkG , dCfg CHdZ ai ESgGdg hJWaFJg GdMQGQI hGddg GdgGOi s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGdKs
(3GdbSe GdKGfi ef GdfLjHjGJs
(3YdjgG ebGHdI SfI (B907 (3g`s
(3hHgG HYV BKGQ QWhHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B280 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B31s
(3agQS GdWH (B- (3U (B195 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B268 s
Keywords: (3GdWHs